Evaluating the Impact of 20 Hours Free Early Childhood Education on Mothers' Labour Force Participation and Earnings - Isabelle Bouchard; Lydia Cheung; Gail Pacheco (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2018)
New Zealand introduced a substantial childcare subsidy just over a decade ago, providing 20 hours free early childhood education (ECE) to all three- and four-year-olds. We evaluate the impact of this policy shift on mothers' labour market participation and earnings. Using a difference-in-differences strategy and population-wide administrative panel data, we follow mothers' quarterly earnings from pre-pregnancy to six years post-childbirth. The estimated impact of the ECE reform varies depending on the number of children eligible. For mothers with one child, there is some evidence of a drop in labour market participation and earnings, which potentially indicates this group is using the savings in ECE expenditure, a gain in real income, to consume more non-work time. For mothers with two eligible children, there is an increase in labour market participation, potentially because these households find it more worthwhile to increase ECE consumption and return to work when there are two children who benefit from the policy.
Keywords: C21; H40; J13; J22; 330; Early childhood education; difference-in-differences; mothers' earnings; intertemporal substitution; administrative data